Study of Effect of KCl Concentration on Density and Viscosity of Ethanol-Water Mixed Solvent Systems at 298.5 K - Ummul Khair Asema, Mohamad Asif; Prashant D. Netankar; Anis Ahmed Sheikh (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
The effect of KCl concentration ranging from 2 % to 10 % on density and viscosity ethanol-water mixed solvent systems ranging from 5 % to 40 % has been studied. The data which obtained has been used to calculate the excess viscosity and B coefficient. The result indicates that as the concentration of KCl increases the density and viscosity also increases it is due to the solute-solvent interaction. The KCl solute breaks the solvent-solvent molecules i.e. ethanol-water molecule due to which there is increase in density and viscosity of mixed solvent systems. The increase in excess viscosity which also gives idea about the dispersion types of forces exerts predominant behavior in these mixed solvent systems due to addition of KCl electrolyte.